Radicular cyst of mandibular anterior region: a case report - Katru, Sreekar; Koduri, Sridevi; Budur, Krishnaveni; Nalli, Prashanth Kumar; Mallolu, Vinolia Sharon; Masa, Ankitha (International Journal of Dental Materials, 2024)
The radicular cyst is the most common odontogenic cyst affecting the jaws. It is a chronic inflammatory response in the epithelial cell rests of malassez, usually following pulpal necrosis. Chronic irritation like trauma, microbial infections or chemical injury can predispose radicular cysts. Radicular cysts, also known as Periapical cysts, found at the apices of the nonvital teeth are classified under the cysts of inflammatory origin as the inflammatory products initiate the growth of the epithelial component. This case report presents a radicular cyst involving the mandible in a 25-year-old male patient reported to the Department of Oral Medicine & Radiology with pain in the lower front tooth region. The etiopathogenesis, clinical, radiographic, and histologic findings, along with the differential diagnoses and treatment modalities, were discussed in this case report.